Ordböckernas roll i svenskans grammatiska standardisering - Hannesdóttir, Anna Helga (LexicoNordica, 2000)
During the 18th century the status of Swedish changed from a poorly codified vernacular into a standardized national language. The bilingual Swedish dictionaries played an important part in the standardization process. Standardization is one of the phases of language planning, as presented by Haugen. He defines language planning as “the evaluation of linguistic change”. All the aspects of standardization are included in the lexical description of the vocabulary presented in the dictionaries: the graphization, the lexication and the grammatication of the language. As the lexical perspective puts every single word in focus, the lexicographers had to present a grammatical description that was in many ways superior to what was generally presented in the contemporary grammars. The effects of standardization are far too often neglected in historical linguistics. The lexicographers did not only evaluate linguistic change; in the long run their decisions also affected the very structure of the language. Thus standardization must be accounted for in any description of language change in the 18th century Swedish and onwards.